2017
DOI: 10.3390/su9101898
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Chain-of-Custody Certification in the Czech and Slovak Republic

Abstract: Forest certification is a voluntary verification tool that has been gaining importance within the global sustainability issues as an independent verification tool for sustainable forest management and wood processing industry and as an influencer in private and public purchasing policies and a component of emerging wood harvesting and trade legality schemes. This study focuses on the chain-of-custody (CoC) component of forest certification. A survey of CoC certified companies in the Czech Republic and Slovakia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
2
11
0
2
Order By: Relevance
“…Similar problems connected with certification were mentioned by Giessen et al [77] and Paluš et al [34]. By examining the perceived level of problems related to certification issues, it was revealed that FSC-certified forest owners perceived almost all problems more seriously than PEFC certified ones who only consider the compliance with certification criteria by contractors as a more problematic issue.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Similar problems connected with certification were mentioned by Giessen et al [77] and Paluš et al [34]. By examining the perceived level of problems related to certification issues, it was revealed that FSC-certified forest owners perceived almost all problems more seriously than PEFC certified ones who only consider the compliance with certification criteria by contractors as a more problematic issue.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the certified owners in particular understand certification as a tool for presenting their improved forest management practices and, consequently, developing their environmental performance [24,34,35,37,41,42,44,45]. On the other hand, neither the certified nor non-certified forest owners consider the economic role of certification to be an important one.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations